Bahtsul Masail as Deliberative Pedagogy in the Formation of Religious Moderation - Mohammad Fadil; Isroqunnajah; Badruddin; Sandi Ferdy Yulianto (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Religious moderation has become an important concern in Islamic education amid growing challenges of intolerance, exclusivism, and religious polarization. While previous studies have highlighted the role of pesantren in fostering moderate religious attitudes, limited attention has been paid to how Bahtsul Masail functions as a deliberative pedagogical process through which religious moderation is formed. This study examines Bahtsul Masail as a deliberative pedagogy in the formation of religious moderation at Al-Falah Ploso Kediri Islamic Boarding School. This study employed a qualitative case study approach using semi-structured interviews, participant observation, and document analysis. Participants consisted of kiai, mushohih, formulators, administrators of the Lajnah Bahtsul Masail, and santri delegates selected through purposive sampling. The findings reveal that Bahtsul Masail operates through a structured deliberative system characterized by active participation, dialogical interaction, and scientific dialectics. Religious knowledge is constructed through processes of argument presentation, critical examination, negotiation of meaning, and scholarly validation. These interconnected processes create a deliberative learning environment in which participants critically engage with diverse religious perspectives. Religious moderation emerges not primarily through doctrinal transmission but through reflective, participatory, and dialectical learning experiences that cultivate tolerance, openness, and contextual understanding. This study proposes the Dialectical-Participatory Model, which explains religious moderation as the outcome of interactions among institutional structure, deliberative pedagogy, scientific dialectics, and scholarly legitimacy. The model contributes to the literature on Islamic education by offering a conceptual framework for understanding how traditional pesantren practices promote both knowledge construction and moderate religious attitudes.